PENGARUH CORPORATE GOVERNANCE DAN AUDITOR EKSTERNAL TERHADAP INTEGRITAS LAPORAN KEUANGAN - Adi Kurniawan Arif Widodo, 09.05.52.0142; Sri Mindarti, Ceacilia (Students Journal of Accounting and Banking, 2014)
This study aims to analyze the influence of institutional ownership, independent directors, independent audit committees and external auditors to integrity of the financial statements.Population in this study were manufacturing company that listed in Indonesian Stock Exchange. Sampling method that used in this study was purposive sampling. Regression analysis was used to testy the influence of institutional ownership, independent directors, independent audit committees and external auditors to integrity of the financial statements.The result of this study showed that institusional ownership, committees audit and external auditors have no influence to integrity of financial statement. On the other the independent directors has a negative influence to integrity of financial statements.Keywords: institutional ownership, independent commissioner, audit committee, external auditors and the integrity of the financial statements